Chickpea (Cicer arietinum L.) battling against heat stress: plant breeding and genomics advances - Jha, Chand Uday; Naik, Yogesh Dashrath; Priya, Manu; Nayyar, Harsh; Sofi, Parvaze A.; Beena, Radha; Kudapa, Himabindu; Atta, Kousik; Thudi, Mahendar; Prasad, Vara P. V.; Siddique, Kadambot H. M. (Springer, 2025)
Global climate change, particularly the increasing frequency and intensity of heat stress, poses a significant threat to crop productivity. Chickpea (Cicer arietinum L.) employs various physiological, biochemical, and molecular mechanisms to cope with elevated temperatures, including maintaining leaf chlorophyll content to preserve the functional integrity of photosystem II (PSII) and enhancing canopy temperature depression to reduce overheating. These traits are crucial for sustaining photosynthetic efficiency, plant health, and yield stability under heat stress. Recent advances in multi-omics approaches—including genomics, transcriptomics, proteomics, and metabolomics—have enhanced our understanding of the genetic basis of heat stress tolerance in chickpea. These tools have facilitated the identification of key genes and molecular pathways involved in heat stress responses. Functional characterization of these genes has provided insights into their roles within the complex metabolic and signaling networks that underpin heat resilience. This review explores integrating conventional and modern breeding technologies with high-throughput phenotyping (HTP) platforms to accelerate genetic gains in chickpea under heat stress. HTP tools enable rapid, precise screening of heat-resilient traits, facilitating early selection of superior genotypes. We also highlight recent genomic advancements, including genome-wide association studies, whole-genome resequencing, and pangenome assemblies, which have uncovered novel structural variants, candidate genes, and haplotypes associated with heat tolerance. Leveraging these resources in conjunction with functional analyses offers new opportunities for breeding climate-resilient chickpea cultivars capable of delivering stable yields and quality under adverse conditions. These developments are crucial for safeguarding chickpea productivity and ensuring global food and nutrition security amid climate change.